Fungal association and utilization of phosphate by plants: success, limitations, and future prospects - Johri, Atul K.; Oelmüller, Ralf; Dua, Meenakshi; Yadav, Vikas; Kumar, Manoj; Tuteja, Narendra; Varma, Ajit; Bonfante, Paola; Persson, Bengt L.; Stroud, Robert M. (Frontiers in Microbiology, 2015)
Phosphorus (P) is a major macronutrient for plant health and development. The available form of P is generally low in the rhizosphere even in fertile soils. A major proportion of applied phosphate (Pi) fertilizers in the soil become fixed into insoluble, unavailable forms, which restricts crop production throughout the world. Roots possess two distinct modes of P uptake from the soil, direct and indirect uptake. The direct uptake of P is facilitated by the plant’s own Pi transporters while indirect uptake occurs via mycorrhizal symbiosis, where the host plant obtains P primarily from the fungal partner, while the fungus benefits from plant-derived reduced carbon. So far, only one Pi transporter has been characterized from the mycorrhizal fungus Glomus versiforme (GvPT). As arbuscular mycorrhizal fungi cannot be cultured axenically, their Pi transporter network is difficult to exploite for large scale sustainable agriculture. Alternatively, the root-colonizing endophytic fungus Piriformospora indica can grow axenically and provides strong growth-promoting activity during its symbiosis with a broad spectrum of plants. P. indica contains a high affinity Pi transporter (PiPT) involved in improving Pi nutrition levels in the host plant under P limiting conditions. As P. indica can be manipulated genetically, it opens new vistas to be used in P deficient fields.